Multi-omics profiling of TGF-β isoforms and regulatory miRNAs in astrocytic tumors reveals TGF-β-3 as a prognostic biomarker - Skóra, Klaudia; Strojny, Damian; Sobański, Dawid; Staszkiewicz, Rafał; Bryś, Kamil; Gogol, Paweł; Bereza, Krzysztof; Masternak, Michalina; Grabarek, Beniamin Oskar (Frontiers in Oncology, 2025)
BackgroundAstrocytic tumors, particularly glioblastomas, are aggressive brain malignancies with poor prognosis. Transforming growth factor-beta (TGF-β) isoforms—TGF-β-1, TGF-β-2, and TGF-β-3—play critical roles in glioma progression, yet their isoform-specific expression patterns and regulatory mechanisms remain incompletely defined. This study aimed to evaluate the differential expression of TGF-β isoforms and their regulation by epigenetic mechanisms and microRNAs (miRNAs) across astrocytic tumor grades.MethodsSixty-five astrocytic tumor samples (WHO grades 2-4) were analyzed. Gene and protein expression of TGF-β-1, -2, and -3 were assessed using reverse transcription quantitative polymerase chain reaction (RT-qPCR), enzyme-linked immunosorbent assay (ELISA), and immunohistochemistry (IHC). Promoter methylation was analyzed using methylation-specific PCR (MSPCR). Differentially expressed regulatory miRNAs were identified by microarray and in silico target prediction. Survival associations were evaluated by Kaplan–Meier and Cox regression analyses.ResultsTGF-β-1 and TGF-β-3 were significantly upregulated in high-grade astrocytomas (p < 0.05), whereas TGF-β-2 showed no consistent changes. TGF-β-3 expression strongly correlated with poor survival (Exp(B) = 1.02644, p < 0.0001), while TGF-β-1 showed a weaker, non-significant association. Among regulatory miRNAs, hsa-miR-2278 (targeting TGF-β-3) was upregulated and significantly associated with worse survival (Exp(B) = 1.437, p = 0.008), while hsa-miR-3196 (targeting TGF-β-1) was downregulated and trended toward better prognosis (Exp(B) = 0.8897, p = 0.076).ConclusionTGF-β-3 is a potent prognostic biomarker in astrocytic tumors and a promising candidate for targeted therapeutic intervention. Regulatory miRNAs such as hsa-miR-2278 and hsa-miR-3196 may serve as molecular modulators of TGF-β signaling and potential adjuncts in personalized glioma therapy. These findings warrant further investigation into miRNA-based therapeutics targeting the TGF-β axis in high-grade gliomas.